Silicon Raj : making a difference to America's future - Rocamora, Rick (2001)
[Dt.:] Silicon Raj ist ein fortlaufendes Fotoprojekt, welches die Leistungen der indischen Einwanderer in den USA dokumentieren und zugleich honorieren soll. Wie der Fotograf hervorhebt, haben indische Einwanderer besonders in den Bereichen HighTech-Industrie, Medizin, Biotechnologie, Verlagswesen, Wissenschaft, Soziale Dienste sowie Kunst und Kultur die Entwicklung in den USA entscheidend mitgeprägt. Daher soll mit dieser Fotoausstellung das Engagement der indischen Einwanderer gewürdigt werden. - [Engl.:] Silicon Raj is a photo documentary work in progress, a project to honor the contributions of Indians in America – in the high tech industry, medicine, biotechnology, publishing, academia, social service, arts and culture – and their entrepreneurial leadership in creating jobs and prosperity for all Americans. The project is also the effort of the photographer to provide the Indian community with a visual voice, so others will respect their ambitions, culture, music, and other social values, and to document the day to day life of a proud community.